When Are Employers Interested in Electronic Performance Monitoring? Results from a Factorial Survey Experiment - Luisa Wieser; Martin Abraham; Claus Schnabel; Cornelia Niessen; Mauren Wolff (Institute of Labor Economics (IZA), 2023)
This paper examines what affects supervisors' considerations about (not) using monitoring technologies to keep track of their subordinates and their work performance. Following a cost-benefit calculus approach we hypothesize that employers weigh costs and benefits of monitoring their subordinates to decide if employee performance monitoring (EPM) is beneficial to their ends. Thus, we conduct a factorial survey experiment (N = 494 supervisors). The hypothetical descriptions of workplace situations – so-called vignettes – were designed to create a situation where the surveyed supervisor is faced with a new team of subordinates and a given technology that can be used to track employees at work. Several components of the situation were randomly varied across vignettes and respondents. At the end of each situation, we asked our respondents to rate their interest to use a given monitoring technology in the described scenario. We find that supervisors are less interested in using monitoring technologies if the monitoring technology targets people rather than tasks and if the time effort for the supervisor is high. However, supervisors' monitoring interest increases if their subordinates interact with sensitive (firm) data and the data evaluation is AI supported. Further, we find that works councils play a role regarding supervisors' monitoring interest. Thus, our results support the thesis that supervisors take the costs and benefits of EPM into consideration regarding their attitude towards monitoring technologies at work.
Keywords: M50; D22; J01; 330; employee performance monitoring; workplace technology; factorial survey experiment; Germany